MRI imaging in pediatric appendicitis - Robin Riley; James Murphy; Timothy Higgins (Elsevier, 2018)
An 8-year-old male presents with two days of abdominal pain and emesis. Computed tomography was concerning for obstruction or reactive ileus with an apparent transition point in the right lower quadrant, possibly due to Crohn's. Magnetic resonance imaging was concerning for perforated appendicitis. As demonstrated by this case MRI can be as sensitive as CT in detecting pediatric appendicitis [2]. We recommend using MRI instead of CT to diagnose appendicitis to avoid ionizing radiation and increased cancer risk in the pediatric population. Keywords: Computer tomography, Magnetic resonance imaging, Pediatric appendicitis